Design and Implementation of a Multimedia-based Technology Solution to Assist Children with Intellectual Disability to Learn - Abou El-Seoud, Samir; Alja'am, Jihad; Mwinyi, Masoud (International Journal of Emerging Technologies in Learning (iJET), 2017)
This paper presents an innovative technological solution to improve the understanding and cognitive functions of children with intellectual disability through multimedia. New algorithms that mine the story-based scripts, rank their sentences, extract keywords and match them with multimedia have been proposed in our previous work. They are integrated in the proposed system and being assessed over 50 stories for children. The results showed that the children concentration and refection are highly improved using multimedia. The system is fully dynamic and support the personalized learning. Instructors can focus on the main ideas of the story which are extracted automatically and use then images and clips to explain them. The words and images are stored in a corpus which is enriched continuously. Every new story taught will add new information to the corpus and to every children dataset. Parents can review the tutorials used in school with their children at home. The system contributes to the reintegration of children with intellectual disability into the society and break their marginalization and isolation.